Spontaneous Superficial Parenchymal and Leptomeningeal Hemorrhage in Term Neonates - Huang, Amy H.; Robertson, Richard L. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Intracranial hemorrhage in term neonates often results from asphyxia, obvious birth trauma, blood dyscrasia, or vascular malformation but may occur without an obvious inciting event. In this study, we review the clinical and neuroimaging features of healthy term neonates presenting with spontaneous superficial parenchymal and leptomeningeal (ie, subpial or subarachnoid) hemorrhage.METHODS: The clinical records and neuroimaging studies of seven term neonates with spontaneous superficial parenchymal and leptomeningeal hemorrhage were retrospectively reviewed. All underwent diffusion-weighted MR imaging and 6 underwent CT within 72 hours of birth. Magnetic susceptibility-weighted imaging was performed in five, MR angiography in two, and MR venography in two. Follow-up MR imaging was performed in one infant. Clinical follow-up was done in four patients.RESULTS: All neonates had normal birth weights and high 5-minute APGAR scores. All were delivered vaginally (one with forceps assistance, and one with vacuum assistance). No blood dyscrasias were noted. Within 36 hours after delivery, all neonates presented with apnea or seizures or both. Neuroimaging subsequently revealed superficial parenchymal and leptomeningeal hemorrhage. Four occurred in the anterior-inferior-lateral temporal lobe adjacent to the pterion. The remaining three were located in the parietal lobe, frontal lobe, and lateral temporal lobe under the squamosal suture. Decreased diffusion in parenchyma adjacent to the hemorrhage and overlying subcutaneous soft-tissue swelling were apparent in five patients. Susceptibility-weighted imaging showed no additional lesions. MR angiography and MR venography findings were normal. Follow-up MR imaging in one patient demonstrated encephalomalacia. Four patients with short-term clinical follow-up were neurologically normal.CONCLUSION: Spontaneous superficial parenchymal and leptomeningeal hemorrhage occurs in otherwise healthy term neonates. The hemorrhage is most often in the temporal lobe and in proximity to sutures, accompanied by overlying soft-tissue swelling and adjacent decreased diffusion. This pattern leads us to implicate local trauma with contusion or venous compression or occlusion in the development of these hemorrhages.